2019
DOI: 10.3390/en12132608
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation of Non-Simultaneous Ice Crushing Force for Wind Turbine Towers with Large Slopes

Abstract: When the offshore wind energy industry attempts to develop in cold regions, ice load becomes the main technological challenge for offshore wind turbine foundation design. Dynamic ice loads acting on wind turbine foundations should be calculated in a reasonable way. The scope of this study is to present a numerical model that considers the non-simultaneous ice crushing failure acting on the vertical structure of a wind turbine’s foundation. The local ice crushing force at the contact surface between the ice she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Lu et al and Wang et al carried out numerical simulations of interactions between level ice and sloping structure using the cohesive element method [17,18]. Zhou et al proposed a numerical model to simulate the non-simultaneous crushing force acting on the cylindrical structures of wind turbines [19]. It was observed that the simulation results agree well with the measured data from the model tests in terms of the maximum ice force.…”
Section: Introductionmentioning
confidence: 89%
“…Lu et al and Wang et al carried out numerical simulations of interactions between level ice and sloping structure using the cohesive element method [17,18]. Zhou et al proposed a numerical model to simulate the non-simultaneous crushing force acting on the cylindrical structures of wind turbines [19]. It was observed that the simulation results agree well with the measured data from the model tests in terms of the maximum ice force.…”
Section: Introductionmentioning
confidence: 89%
“…Numerical modeling is a common method for analyzing the bearing capacity of foundations [36][37][38], which has the advantages of an unlimited number of test samples and a high flexibility of the simulation scheme.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…With the rapid development of numerical simulation technology, non-linear dynamics calculation methods have been gradually introduced in the research of sea ice and OWT collision problems. A non-simultaneous ice force model of sea ice acting on a vertical OWT structure was proposed by Zhou et al (2019); the results showed that the proposed numerical model can capture the main trends of ice-wind turbine foundation interaction. Jaakko and Simo (2017) studied different load combinations when coupling wind, ice and structure.…”
Section: Introductionmentioning
confidence: 99%